Self-repairing agent for oil well cement, and preparation method and application thereof

CN118290052BActive Publication Date: 2026-10-30CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310004106.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-01-03
Publication Date
2026-10-30
Estimated Expiration
2043-01-03

AI Technical Summary

Technical Problem

[0006]刺激响应型聚合物技术中使用的聚合物通常为吸油树脂或弹性体胶乳,虽然具有较好的自修复效果,但这些聚合物的耐热性和耐久性都不好,限制了其在工程上的应用

Benefits of technology

[0038]1、本发明的自修复剂具有较好的亲和性,能够均匀稳定的分散在水泥浆中,方便进行工程化应用。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118290052B_ABST
    Figure CN118290052B_ABST
Patent Text Reader

Abstract

The application discloses a self-repairing agent for oil well cement, a preparation method and application thereof, and the self-repairing agent comprises at least surface sulfonated thermoplastic elastomer particles, the thermoplastic elastomer particles comprise rubber, polyolefin and inorganic filler, wherein the weight ratio of the rubber to the polyolefin is 1:4-4:1, and the density of the inorganic filler is 1.5-8 g / cm 3 The self-repairing agent has good affinity, can be uniformly and stably dispersed in cement slurry, and is convenient for engineering application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of cement slurry materials for oil and gas field cementing, and specifically relates to self-healing agents for oil well cement, their preparation methods, and applications. Background Technology

[0002] Cementing is a crucial link between drilling operations and oil and gas resource development. The procedure includes running casing of a specific size downhole, followed by injecting cement slurry into the annulus between the casing and the wellbore using a pump after casing installation. This hydraulic cement slurry hardens into a cement sheath within a certain timeframe. The functions of the cement sheath include supporting the casing and preventing corrosion from formation fluids, isolating lost circulation zones and collapsed zones in complex formations, and isolating oil, gas, and water layers to lay the foundation for stratified resource development. High-quality cement sheaths should maintain long-term sealing integrity, which is crucial for the production life of oil and gas wells and directly affects subsequent oil and gas production. However, due to impact loads, complex formation movements, and long-term chemical corrosion from corrosive media, cement sheath cracking in oil wells leads to oil and gas leakage, a global problem causing significant economic losses. Therefore, repairing cracks in the cement sheath is essential.

[0003] Currently, the main cement sheath repair technologies in China and abroad include cement extrusion operations and self-healing technologies for microcracks in cement-based materials. The former has high operational risks, low success rates, and high costs, making it unsuitable for further development in cementing operations; while the latter has been widely applied to the self-healing of cement-based materials and is one of the research hotspots in cement cementing, mainly including liquid core or hollow fiber, microcapsules, thermally reversible crosslinking reactions, and stimulus-responsive polymer technologies.

[0004] Liquid core or hollow fiber technology and microcapsule technology involve pre-placing a repair agent in a cement matrix. The repair agent is placed inside a coating material. Once affected by factors such as pressure or temperature, the coating material ruptures and releases the repair agent to repair the cracks. However, this technology has high requirements for the coating material.

[0005] Thermally reversible crosslinking technology involves pre-inserting a crosslinked polymer with thermally reversible reaction properties into a cement matrix, enabling repeated repairs in response to changes in ambient temperature. However, the high research cost of this technology limits its practical application. Stimulus-responsive polymer technology involves pre-inserting a polymer material that responds to oil and gas. Upon contact with oil and gas, it absorbs and expands, thereby sealing gaps and achieving a self-healing effect.

[0006] The polymers used in stimulus-responsive polymer technologies are typically oil-absorbing resins or elastomer latexes. While these polymers exhibit good self-healing properties, their poor heat resistance and durability limit their engineering applications. Crucially, the polymers used in stimulus-responsive polymer technologies are usually non-polar materials with low density, while cement slurry is a polar material with high density, high pH, ​​and high salt concentration. This poor compatibility between the two hinders effective application, and no effective solutions to these problems have yet been found.

[0007] Chinese patent CN105952413A reports a self-healing cement containing styrene-butadiene-styrene or styrene-isoprene-styrene polymer particles, but the heat resistance of the polymer is limited, which is not conducive to its application. Summary of the Invention

[0008] The purpose of this invention is to overcome the shortcomings of the prior art and provide a surface self-healing agent for cement slurry in oil and gas fields, its preparation method and application. Adding this self-healing agent to the cement slurry can produce a cement slurry with uniform dispersion and stable performance. After the cement slurry is cured, the elastic modulus of the cement stone formed is significantly reduced compared with conventional cement stone, and it has self-healing properties when exposed to oil and gas, thereby ensuring the long-term sealing of the cement sheath.

[0009] The objective of this invention is achieved through the following technical solutions.

[0010] In a first aspect, the present invention provides a self-healing agent for oil well cement, the self-healing agent comprising at least surface-sulfonated thermoplastic elastomer particles, the thermoplastic elastomer particles comprising rubber, polyolefin, and inorganic filler, wherein the weight ratio of the rubber to the polyolefin is 1:4-4:1, and the density of the inorganic filler is 1.5-8 g / cm³. 3 .

[0011] In this invention, it is not intended to be limited by theoretical considerations. By adjusting the ratio of rubber and polyolefin, the melting point of the product can be made near the temperature of the cement paste formation. When natural gas rises through the cracks, the molten product adheres to the cracks, preventing oil and gas from rising. The polyolefin in the self-healing agent has the ability to expand upon contact with oil and gas, and after expansion, it can also block the channels for oil and gas to rise. Furthermore, the addition of weighting materials (inorganic fillers) to the self-healing agent makes the product density similar to that of the cement paste, allowing it to disperse evenly in the cement paste without floating. Further, at least the surface of the self-healing agent is sulfonated, changing the product surface from oleophilic to hydrophilic, resulting in a granular dispersion in the cement paste without agglomeration. Additionally, it is believed that the hydrophilic properties of the sulfonated thermoplastic elastomer particles do not change under high temperature and pressure, the chemical properties of the rubber and polyolefin do not change in the high-temperature cement paste, and the properties of the inorganic filler remain unchanged at high temperatures. Therefore, the self-healing agent of this invention exhibits good heat resistance and durability.

[0012] According to the self-healing agent provided by the present invention, the particle size of the self-healing agent is 20-200 mesh, preferably 60-80 mesh.

[0013] According to the self-healing agent provided by the present invention, the rubber is one or a combination of ethylene propylene diene monomer (EPDM), butyl rubber, and natural rubber; and / or, the polyolefin is one or a combination of polyethylene and polypropylene. For example, EPDM and / or butyl rubber with a number average molecular weight of 50,000-100,000 g / mol can be used. For example, polyethylene and / or polypropylene with a number average molecular weight of 50,000-100,000 g / mol can be used.

[0014] In this invention, the ethylene structural unit content of the EPDM rubber can be 30-40% by weight, the propylene structural unit content can be 30-40% by weight, and the 1,6-hexadiene structural unit content can be 20-30% by weight.

[0015] According to the self-healing agent provided by the present invention, the weight ratio of the rubber to the polyolefin can be 1:4, 2:3, 3:2, 4:1, or a range thereof. In some embodiments, the weight ratio of the rubber to the polyolefin can be 2:3-3:2.

[0016] According to the self-healing agent provided by the present invention, the density of the inorganic filler is 2-6 g / cm³. 3 Preferably 3-5g / cm 3 In this invention, suitable examples of inorganic fillers include, but are not limited to: calcium carbonate, barium sulfate, iron ore powder, cement, and quartz sand.

[0017] According to the self-healing agent provided by the present invention, the amount of the inorganic filler is 0.4-3 times the total mass of the rubber and polyolefin. For example, the amount of the inorganic filler is 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.25, 1.5, 1.75, 2, 2.5, 3 times, or a range thereof, of the total mass of the rubber and polyolefin. In some embodiments, the amount of the inorganic filler is 0.5-2.5 times the total mass of the rubber and polyolefin, preferably 0.7-1.5 times.

[0018] According to the self-healing agent provided by the present invention, the thermoplastic elastomer particles are sulfonated thermoplastic elastomer particles.

[0019] Secondly, the present invention provides a method for preparing a self-healing agent, comprising the following steps:

[0020] S1. Rubber, polyolefin and inorganic filler are melt-blended and granulated to obtain thermoplastic elastomer particles;

[0021] S2. The thermoplastic elastomer particles are sulfonated to obtain the self-healing agent.

[0022] According to the preparation method provided by the present invention, the sulfonation treatment in step S2 includes:

[0023] S210. Disperse the thermoplastic elastomer particles in a first solvent to dissolve and / or swell the thermoplastic elastomer particles to obtain a first dispersion.

[0024] S220. Add a sulfonating agent to the first dispersion for sulfonation treatment to obtain thermoplastic elastomer particles with at least surface sulfonation treatment.

[0025] According to the preparation method provided by the present invention, the sulfonating agent is one or a combination of concentrated sulfuric acid, fuming sulfuric acid, chlorosulfonic acid, and acetylsulphate.

[0026] According to the preparation method provided by the present invention, the sulfonation temperature is -10°C to 30°C; and / or the sulfonation time is 5-20 hours.

[0027] In some embodiments, the sulfonation treatment in step S2 includes:

[0028] S210. The thermoplastic elastomer particles are dispersed in a first solvent to dissolve the rubber and polyolefin in the thermoplastic elastomer particles, thereby obtaining a first dispersion.

[0029] S220. Sulfonating agent is added to the first dispersion for sulfonation treatment, and a second solvent is added for precipitation. After filtration and washing, thermoplastic elastomer particles with at least surface sulfonation treatment are obtained.

[0030] According to the preparation method provided by the present invention, the first solvent is selected from at least one of dichloromethane, trichloromethane, and tetrachloromethane.

[0031] According to the preparation method provided by the present invention, the mass-to-volume ratio of the thermoplastic elastomer particles to the first solvent is 10-30:100g / ml.

[0032] According to the preparation method provided by the present invention, the second solvent is selected from methanol, ethanol, or a combination thereof.

[0033] According to the preparation method provided by the present invention, the volume ratio of the second solvent to the first solvent is 1:2-5.

[0034] Thirdly, the present invention provides a self-healing agent prepared by the above method.

[0035] Fourthly, the present invention provides the application of the self-healing agent in the field of oil and gas field cementing.

[0036] According to the application provided by the present invention, the application includes adding the self-healing agent to cement slurry for cementing; preferably, the self-healing agent accounts for 5-15% of the weight of cement in the cement slurry.

[0037] Compared with the prior art, the beneficial effects of the present invention are:

[0038] 1. The self-healing agent of the present invention has good affinity and can be uniformly and stably dispersed in cement slurry, which facilitates its engineering application.

[0039] 2. The self-healing agent of the present invention has a density similar to that of cement slurry, does not separate into layers, and is evenly dispersed in cement slurry.

[0040] 3. The self-healing agent of the present invention has the characteristics of fast oil and gas absorption speed, high multiplier, good heat resistance, good durability, and excellent mechanical properties of the expanded body. Attached Figure Description

[0041] Figure 1 This is a curve showing the flow rate variation of self-healing cement stone cracks using the self-healing agent of this invention. Detailed Implementation

[0042] The present invention will be further described below with reference to embodiments. The following embodiments are illustrative and not limiting, and should not be used to limit the scope of protection of the present invention.

[0043] Example 1

[0044] The composition, by weight percentage, consists of 30% ethylene propylene diene monomer (EPDM) rubber (number average molecular weight 89300 g / mol, ethylene structural unit content 33 wt%, propylene structural unit content 37.7 wt%, 1,6-hexadiene structural unit content 29.3 wt%), 20% polypropylene (number average molecular weight 76910 g / mol, degree of hydrogenation 95.3%), and 50% precipitated barium sulfate (particle size 15 micrometers, density 4.4 g / cm³). 3 The mixture is thoroughly mixed and melt-blended at 230°C using a twin-screw extruder. After granulation, freeze-drying, and passing through a 40-mesh sieve, thermoplastic elastomer granules are obtained.

[0045] Using chloroform (CHCl3) as solvent, add 10g of acetic anhydride and stir at a constant speed. When the temperature drops below 5℃, add 5g of concentrated sulfuric acid dropwise. After reacting for 30min, remove it from the ice bath and stir rapidly at room temperature for 10min to obtain fresh acetyl sulfate.

[0046] 20g of thermoplastic elastomer granules were added to a three-necked flask containing 100ml of CHCl3 and stirred to dissolve. An appropriate amount of 2g of prepared acetylsulphuric acid was added as a sulfonating agent to initiate the sulfonation reaction. After 24 hours of reaction, 400ml of methanol was added under rapid stirring to terminate the reaction, simultaneously generating a granular polymer precipitate. The precipitate was filtered, washed with methanol until neutral, dried in a vacuum drying oven at 40℃, pulverized, and passed through a 60-mesh sieve to obtain the self-healing agent. The actual density of this self-healing agent is 1.45g / cm³. 3 The cement slurry is uniformly mixed with cement slurry used for cementing in oil and gas fields to obtain self-repairing cement slurry. Based on the total amount of cement in the cement slurry, the content of the composition is 10% by weight, stirred and cured at 90°C for 20 minutes, and left to stand at room temperature for 2 hours. The density difference of the cement slurry Bp is 0.

[0047] Example 2

[0048] The composition, by weight percentage, consists of 20% butyl rubber (number-average molecular weight 65270 g / mol), 30% polyethylene (number-average molecular weight 53900 g / mol, degree of hydrogenation 95.3%), and 50% calcium carbonate (particle size 24 micrometers, density 2.7 g / cm³). 3 The mixture is thoroughly mixed and melt-blended at 230°C using a twin-screw extruder. After granulation, freeze-drying, and passing through a 40-mesh sieve, thermoplastic elastomer granules are obtained.

[0049] 20g of thermoplastic elastomer granules were added to a three-necked flask containing 100ml of 1,2-dichloroethane. The mixture was stirred electrically at low temperature for 1 hour. Without affecting the stirring or maintaining the viscosity, 2g of a mixture of acetic anhydride and concentrated sulfuric acid (molar ratio 2:1) was added to initiate a sulfonation reaction. After 24 hours of reaction, 400ml of methanol was added with rapid stirring to terminate the reaction, resulting in a granular polymer precipitate. The precipitate was filtered, washed with methanol until neutral, dried in a vacuum drying oven at 40℃, pulverized, and passed through a 60-mesh sieve to obtain the self-healing agent. The actual density of the self-healing agent granules was 1.23g / cm³. 3 The cement slurry is uniformly mixed with cement slurry used for cementing in oil and gas fields to obtain a self-repairing cement slurry. Based on the total amount of cement in the cement slurry, the content of the composition is 10% by weight. After stirring and curing at 90°C for 20 minutes and standing at room temperature for 2 hours, the density difference of the cement slurry (Bp) is 0.02 g / cm³. 3 .

[0050] Example 3

[0051] The mixture comprises, by weight percentage, 30% natural rubber, 10% polyethylene (number average molecular weight 53900 g / mol, hydrogenation degree 95.3%), 10% polypropylene (number average molecular weight 76910 g / mol, hydrogenation degree 95.3%), and 50% Jiahua cement (particle size 20–60 micrometers, density 3.27 g / cm³).3 The mixture is thoroughly mixed and melt-blended at 210°C using a twin-screw extruder. After granulation, freeze-drying, and passing through a 40-mesh sieve, thermoplastic elastomer granules are obtained.

[0052] Sulfonation was performed according to the method described in Example 2. The actual density of the self-healing agent particles was 1.32 g / cm³. 3 The cement slurry is uniformly mixed with cement slurry used for cementing in oil and gas fields to obtain a self-repairing cement slurry. Based on the total amount of cement in the cement slurry, the content of the composition is 10% by weight. After stirring and curing at 90°C for 20 minutes and standing at room temperature for 2 hours, the density difference of the cement slurry (Bp) is 0.01 g / cm³. 3 .

[0053] Example 4

[0054] The composition, by weight percentage, consists of 10% butyl rubber (number-average molecular weight 65270 g / mol), 40% polyethylene (number-average molecular weight 53900 g / mol, degree of hydrogenation 95.3%), and 50% calcium carbonate (particle size 24 micrometers, density 2.7 g / cm³). 3 The mixture is thoroughly mixed and melt-blended at 230°C using a twin-screw extruder. After granulation, freeze-drying, and passing through a 40-mesh sieve, thermoplastic elastomer granules are obtained.

[0055] Sulfonation was performed according to the method described in Example 2. The actual density of the self-healing agent particles was 1.23 g / cm³. 3 The cement slurry is uniformly mixed with cement slurry used for cementing in oil and gas fields to obtain a self-repairing cement slurry. Based on the total amount of cement in the cement slurry, the content of the composition is 10% by weight. After stirring and curing at 90°C for 20 minutes and standing at room temperature for 2 hours, the density difference of the cement slurry (Bp) is 0.02 g / cm³. 3 .

[0056] Comparative Example 1

[0057] 60% ethylene propylene diene monomer (EPDM) rubber (number average molecular weight 89300 g / mol, ethylene structural unit content 33 wt%, propylene content 37.7 wt%, 1,6-hexadiene content 29.3 wt%) and 40% polypropylene (number average molecular weight 76910 g / mol, hydrogenation degree 95.3%) were mixed uniformly by mass percentage, and melt-blended at 230°C using a twin-screw extruder. After granulation, freeze-pulverization, and passing through a 40-mesh sieve, thermoplastic elastomer granules were obtained.

[0058] Using chloroform (CHCl3) as solvent, add 10g of acetic anhydride and stir at a constant speed. When the temperature drops below 5℃, add 5g of concentrated sulfuric acid dropwise. After reacting for 30min, remove it from the ice bath and stir rapidly at room temperature for 10min to obtain fresh acetyl sulfate.

[0059] 20g of thermoplastic elastomer particles were added to a three-necked flask containing 100ml of CHCl3 and stirred electrically until dissolved. Then, 2g of prepared acetylsulphuric acid was added as a sulfonating agent to initiate a sulfonation reaction. After 24 hours of reaction, 400ml of methanol was added with rapid stirring to terminate the reaction, resulting in a granular polymer precipitate. The precipitate was filtered, washed with methanol until neutral, dried in a vacuum drying oven at 40℃, pulverized, and passed through a 60-mesh sieve to obtain the self-healing agent. The actual density of the self-healing agent particles was 0.98g / cm³. 3 The self-healing cement slurry is obtained by uniformly mixing the cement with cement slurry used for cementing in oil and gas fields. Based on the total amount of cement in the cement slurry, the content of the composition is 10% by weight. After stirring and curing at 90°C for 20 minutes and standing at room temperature for 2 hours, the self-healing particles completely float on the top of the cement slurry.

[0060] Comparative Example 2

[0061] The composition, by weight percentage, consists of 30% ethylene propylene diene monomer (EPDM) rubber (number average molecular weight 89300 g / mol, ethylene structural unit content 33 wt%, propylene content 37.7 wt%, 1,6-hexadiene content 29.3 wt%), 20% polypropylene (number average molecular weight 76910 g / mol, hydrogenation degree 95.3%), and 50% precipitated barium sulfate (particle size 15 micrometers, density 4.4 g / cm³). 3 The mixture is thoroughly mixed and melt-blended at 230°C using a twin-screw extruder. After granulation, freeze-drying, and passing through a 40-mesh sieve, thermoplastic elastomer granule precursors are obtained, which serve as self-healing agents.

[0062] The actual density of the self-healing agent particles is 1.43 g / cm³. 3 The self-healing cement slurry is obtained by uniformly mixing the cement with cement slurry used for cementing in oil and gas fields. Based on the total amount of cement in the cement slurry, the content of the composition is 10% by weight. After stirring and curing at 90°C for 20 minutes and standing at room temperature for 2 hours, the self-healing particles agglomerate and do not disperse in the cement slurry.

[0063] Comparative Example 3

[0064] The mixture consists of 50% styrene-butadiene-styrene granules (purchased from ICO Polymers, trade name ICO4, melt index 23-37 g / 10 min at 200℃ / 50 g) and 50% precipitated barium sulfate (particle size 15 micrometers, density 4.4 g / cm³). 3 The mixture is thoroughly mixed and melt-blended at 230°C using a twin-screw extruder. After granulation, freeze-drying, and passing through a 40-mesh sieve, thermoplastic elastomer granules are obtained.

[0065] Sulfonation was performed according to the method in Example 2. The actual density of the self-healing agent particles was 1.38 g / cm³. 3The cement slurry is uniformly mixed with cement slurry used for cementing in oil and gas fields to obtain a self-repairing cement slurry. Based on the total cement content of the cement slurry, the composition content is 10% by weight. The cement slurry is cured in a high-temperature, high-pressure curing autoclave. When the temperature reaches 165°C and the pressure reaches 68 MPa, the temperature-pressure curve shows significant fluctuations. Upon disassembly, it was found that the slurry exhibits a core-encapsulation problem. Conventional cement slurries do not exhibit this type of problem.

[0066] Performance testing

[0067] Cement blocks of 4×4×15cm were prepared using the cement slurry from the above examples and comparative examples. The mechanical properties of the cement blocks from each example after curing at 80℃ for 48 hours are shown in Table 1. The compressive strength and flexural strength were measured according to the national standard GB19139. The cement slurry formula used was: Jiahua cement + 35% quartz sand + 5% fluid loss reducing agent (Sinopec Engineering Institute SCF-Y) + 2-8% retarder (Sinopec Engineering Institute SCH-3) + 10% self-healing agent + 59% water, where the proportions are all percentages of the cement mass.

[0068] Table 1

[0069] Example 1 19.52 6.4 Example 2 14.98 6.3 Example 3 15.43 5.8 Example 4 23.6 5.3

[0070] As shown in Table 1, the addition of cement stone in Example 1 had the least impact on its strength (compressive strength of blank cement stone was 25.8 MPa, and flexural strength was 5.06 GPa), and the flexural strength of the cement stone met the requirements. In Example 4, increasing the polyolefin content significantly improved the compressive and flexural strength of the cement stone.

[0071] Figure 1 The change in flow rate of self-healing cement stone cracks using the self-healing agent of this invention is shown. A simulated cylindrical well with an inner diameter of 5 cm, a wall thickness of 2 cm, and a length of 20 cm was injected with the cement grout from Example 1. This compression of the simulated wellbore created a through-crack, forming a natural gas flow channel with a flow rate of 452 ml / min. The natural gas outlet valve was closed, and the damaged cement stone was pressurized in natural gas at 80°C and 7 MPa for 20 hours. After curing, the natural gas outlet valve was opened, and the natural gas flow rate was tested. The natural gas flow rate rapidly decreased to 0, indicating a 100% repair rate.

[0072] When Example 2, Example 3, and Example 4 were used instead of Example 1 in the above experiment, the self-healing rates of the cement stone were 76%, 37%, and 60%, respectively, and complete repair was not achieved.

Claims

1. A self-healing agent for oil well cement, characterized in that, The self-healing agent comprises at least surface-sulfonated thermoplastic elastomer particles. The raw materials for the thermoplastic elastomer particles include rubber, polyolefin, and inorganic fillers, wherein the weight ratio of the rubber to the polyolefin is 2:3-3:2, and the density of the inorganic filler is 1.5~8 g / cm³. 3 The rubber is one or a combination of ethylene propylene diene monomer (EPDM) rubber and butyl rubber, the polyolefin is one or a combination of polyethylene and polypropylene, and the amount of inorganic filler is 0.4-3 times the total mass of the rubber and polyolefin.

2. The self-healing agent according to claim 1, wherein, The self-healing agent has a particle size of 20-200 mesh.

3. The self-healing agent according to claim 1, wherein, The self-healing agent has a particle size of 60-80 mesh.

4. The self-healing agent according to any one of claims 1-3, wherein, The inorganic filler is one or a combination of calcium carbonate, barium sulfate, iron ore powder, cement, and quartz sand.

5. The self-healing agent according to claim 4, wherein, The density of the inorganic filler is 2-6 g / cm³. 3 .

6. The self-healing agent according to claim 5, wherein, The amount of the inorganic filler is 0.5-2.5 times the total mass of the rubber and polyolefin.

7. The self-healing agent according to claim 5, wherein, The amount of the inorganic filler is 0.7-1.5 times the total mass of the rubber and polyolefin.

8. A method for preparing the self-healing agent according to any one of claims 1-7, characterized in that, Includes the following steps: S1. Rubber, polyolefin and inorganic filler are melt-blended and granulated to obtain thermoplastic elastomer particles; S2. The thermoplastic elastomer particles are sulfonated to obtain the self-healing agent.

9. The preparation method according to claim 8, wherein, The sulfonation treatment in step S2 includes: S210. Disperse the thermoplastic elastomer particles in a first solvent to dissolve and / or swell the thermoplastic elastomer particles to obtain a first dispersion. S220. Add a sulfonating agent to the first dispersion for sulfonation treatment to obtain thermoplastic elastomer particles with at least surface sulfonation treatment.

10. The preparation method according to claim 9, wherein, The sulfonating agent is one or a combination of concentrated sulfuric acid, fuming sulfuric acid, chlorosulfonic acid, and acetylsulphate; And / or, the sulfonation temperature is -10°C to 30°C; and / or, the sulfonation time is 5-20 hours.

11. The preparation method according to claim 9, wherein, In step S220, after adding a sulfonating agent to the first dispersion for sulfonation treatment, a second solvent is added for precipitation. After filtration and washing, thermoplastic elastomer particles with at least surface sulfonation treatment are obtained.

12. The preparation method according to claim 11, wherein, The first solvent is selected from at least one of dichloromethane, trichloromethane, and tetrachloromethane; the mass-to-volume ratio of the thermoplastic elastomer particles to the first solvent is 10-30:100 g / mL; And / or, the second solvent is selected from methanol, ethanol or a combination thereof; the volume ratio of the second solvent to the first solvent is 1:2-5.

13. The application of the self-healing agent according to any one of claims 1-7 or the self-healing agent prepared by the preparation method according to any one of claims 8-12 in the field of oil and gas field cementing.

14. The application according to claim 13, wherein, The application includes adding the self-healing agent to cement slurry used for cementing.

15. The application according to claim 14, wherein, The self-healing agent accounts for 5-15% of the weight of cement in the cement slurry.

Citation Information

Patent Citations

  • Self-Repairing Cements

    CN105952413A

  • Composition for oil-gas well cementation, self-repairing material, preparation method and application of self-repairing material

    CN112391151A

  • Composition and preparation method and application thereof, and well cementation self-repairing method for oil and gas fields

    CN114058035A

  • Methods for maintaining zonal isolation in a subterranean well

    US20170174977A1